Spatial Analysis of Bacteriological and Chemical Quality of Refill Drinking Water in Palembang - Inoy Trisnaini; Fison Hepiman (Faculty of Public Health, Sriwijaya University, 2023)
Research by Trisnaini (2013) in Ogan Ilir Regency found that there were 13 depot refill drinking water which water samples were positive for Coliform. Data by the Environmental Health Engineering Center of Palembang on 136 depot found that not all depot were not suitable with the requirements of Ministry of Health Regulations RI Number492/2010. The impact is low drinking water quality that potentially cause diseases. The purpose of this study was to analyze the quality of depot refill drinking water in the city of Palembang based on the parameters of Coliform, Escherecia Coli, and pH. This research used a quantitative design, with a survey method. The research was conducted in the city of Palembang. The research population was 136 depot refill drinking water in the city of Palembang. Sampling was using proportionate stratified random sampling. Based on the results of laboratory tests, it was found that from 36 depot refill drinking water there were 2 (5.8%) which showed positive results of water samples containing Coliform, 2 (5.8%) which were positive for Escherecia Coli, and most of (91%) water samples examined did not suitable the health requirements on the parameter of pH. It is concluded that most of the water samples from the depot refill drinking water studied had met the health requirements based on the parameters of Coliform and Escherecia Coli, but most did not suitable the health requirements for the pH parameter based on the Ministry of Health Regulations RI Number 492/2010.The need for increased supervision of refill drinking water depots